Social and behavior change communication in the fight against malaria in Mozambique - Arroz, Jorge Alexandre Harrison (Revista de Saúde Pública, 2017)
Long-lasting insecticide-treated nets and/or indoor residual spraying, associated with case management, are key interventions in the control of malaria in Africa. The objective of this study is to comment on the role of social and behavior change communication as a potential key intervention in the control of malaria in Mozambique.